Ionic liquid based pretreatment of lignocellulosic biomass for enhanced bioconversion. (May 2020) - Usmani, Zeba; Sharma, Minaxi; Gupta, Pratishtha; Karpichev, Yevgen; Gathergood, Nicholas; Bhat, Rajeev; Gupta, Vijai Kumar
Graphical abstract: Highlights: Advancements in Ionic Liquid usage for biomass pretreatment as a green alternative. Comparative analysis of Ionic Liquid pretreatment with other common methodologies. Critical analysis of pretreatment modeling and Ionic Liquid solvation parameters. Techno-economic viability of Ionic liquid based commercial scale pretreatment plant. SWOT analysis with identification of knowledge gaps and future research directions. Abstract: Lignocellulosic biomass is the most plentiful renewable biomolecule and an alternative bioresource for the production of biofuels and biochemicals in biorefineries. But biomass recalcitrance is a bottleneck in their usage, thus necessitating their pretreatment for hydrolysis. Most pretreatment technologies, result in toxic by-products or have lower yield. Ionic liquids (ILs) have successfully advanced as 'greener and recyclable' alternatives to volatile organic solvents for lignocellulosic biomass dissolution. This review covers recent developments made in usage of IL-based techniques with focus on biomass breakdown mechanism, process parameter design, impact of cation and anion groups, and the advantageous impact of ILs on the subsequent processing of the fractionated biomass. Progress and barriers for large-scale commercial usage of ILs in emerging biorefineries were critically evaluated using the principles of economies of scale and green chemistry in an environmentally sustainable way.